Synthesis and liquid crystal properties of phthalocyanine bearing a star polytetrahydrofuran moiety - Gursel, Yesim H.; Senkal, B. Filiz; Kandaz, Mehmet; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2009)
A new polymeric ligand, 6-(3,4-dicyanophenylthio)-hexyl-2-polytetrahydrofuranacetate (2) and its liquid crystalline polymeric phthalocyanine, 2,9,16,23-tetrakis-{6-(polytetrahydrofuran-2-carboxylate)hexylthio-phthalocyaninatocobalt(II) (3), {Co[Pc(S-C6H13OCO-poly-THF)(4)]}(CoPcLC) have been synthesized. The ligand and the phthalocyanine, bearing polytetrahydrofuran moieties (poly-THF), were characterized using elemental analysis, FTIR, H-1 and C-13 NMR, and UV-Vis techniques. CoPcLC (3) promotes a greater interaction between the mesogens, resulting in solution aggregations together with a red-shift in the Q-band in the presence of the soft Ag+ ion. The dielectric anisotropy and phase transition temperature values of CoPcLC doped with 4-cyano-4'-n-pentylbiphenyl (5CB) were found to be 7.17 and 40.5 degrees C, respectively. The dielectrical anisotropy behaviour of the liquid crystals changes from the positive to the negative type. The current-voltage characteristics of the liquid crystals show a non-linear behaviour. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Liquid crystal; Cationic; Polymerization; Cobalt; Metal-ion sensing